A Review of Methods to Determine Viability, Vitality, and Metabolic Rates in Microbiology - Braissant, Olivier; Astasov-Frauenhoffer, Monika; Waltimo, Tuomas; Bonkat, Gernot (Frontiers in Microbiology, 2020)
Viability and metabolic assays are commonly used as proxies to assess the overall metabolism of microorganisms. The variety of these assays combined with little information available on some assay kit or online protocols often lead to mistakes or poor interpretation of the results. In this review, the necessary data are compiled to understand the reactions or the measurements performed in many of the assays commonly used in various aspects of microbiology. Also their relations to each other as metabolism is linking many of these assays resulting in correlations between values and parameters measured are discussed. Finally, the limitations of these assays are discussed.